Synthesis and anticancer activity of conformationally constrained Smac mimetics containing pseudo beta turns - Baravkar, Sachin B.; Wagh, Mahendra A.; Paul, Debasish; Santra, Manas; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2018)
Herein, we report synthesis and in vitro anticancer activity of conformationally constrained Smac mimetics containing reverse turn inducing motifs "Ant-Pro" and "sAnt-Pro". The synthesis of Smac analogs with diverse hydrophobic groups at the C-terminus was carried out using solution phase peptide synthesis. The synthesis of Ant-Pro containing analogs 3a-j was carried out by ring opening of benzoxazinones 7a-c, whereas, their sulfonamide counterparts 4a-h were synthesized by using routine acid-amine coupling reaction. In vitro anticancer studies against breast cancer cell line MDA-MB-231 revealed that some of the new analogs had better anticancer activity than the standard AVPI Smac tetrapeptide. (C) 2018 Published by Elsevier Ltd.

Repurposed ciprofloxacin derivatives as potent autophagic-type anticancer agents - Gone, Nilu Vijay; Sharma, Tanisha; Joshi, Rakesh; Upreti, Akshita; Santra, Manas; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2026)
Drug repurposing - also known as drug repositioning is a proven strategy for identifying new therapeutic uses for existing and pre-approved drugs with considerable success in recent years. Herein, we report the discovery of a novel class of ciprofloxacin-amino acid conjugates that are dynamically potent against different cancer cell lines. Some of the molecules reported herein displayed a strong anti-proliferative effect on MCF-7 (IC50: 6 mu M). The most active anti-proliferative molecule of this series 7a suppressed the proliferation of HCT116, A549, and MDAMB-231 cancer cell lines. Furthermore, we established that the treatment with 7a leads to DNA damage-mediated autophagic cell death in cancer cells. Our findings suggest that appropriate derivatization of the ciprofloxacin drug can yield promising anti-cancer compounds in easy synthetic operations.
Keywords: Anticancer drugs; Autophagic cell death; ciprofloxacin